BEBERAPA TEMUAN PRASASTI BARU DI INDONESIA - Sukarto Karto Atmodjo (Berkala Arkeologi, 1994)
In the context of my retirement as an epigraphy officer from the Balai Arkeologi Yogyakarta, I will briefly review some of the findings of new inscriptions in Kalimantan, Sumbawa, Sumatra and Java. However, I need to explain that two of the findings, namely in Kalimantan, have long been discovered and researched by experts, but until now they have not been completed. The findings are actually quite a lot, but on this good occasion and time (subha diwasa), I will only briefly review some of the findings.